INTERNATIONAL PROJECT PARTICIPATION BY WOMEN ACADEMICS - Arthur, Nancy; Patton, Wendy; Giancarlo, Christine (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
The internationalization of higher education has led to changing roles for academics, including opportunities to participate in international projects. The extent to which academics feel prepared to enter this arena has received little attention. This study examines women academics’ perceptions of barriers to, facilitators of, and career benefits of pursuing international projects. Thirteen women academics participated in semi‐structured interviews that illuminated six core themes: the benefits of international roles, influences on motivation, enablers and barriers, expanded personal and academic world views, and ways of gaining international competencies. Suggestions are given for supporting academic women to pursue international opportunities. Key words: women’s career development, women academics, internationalization communities L’internationalisation des études supérieures entraîne une évolution dans les rôles des professeurs, qui se voient ainsi entre autres offrir la possibilité de participer à des projets internationaux. Dans quelle mesure les professeurs se sentent‐ils prêts à entrer dans cette arène? Voilà une question qui a peu été analysée. Cette étude porte sur les perceptions qu’ont des universitaires de sexe féminin sur les obstacles à la participation à des projets internationaux, les facteurs qui la facilitent et les impacts positifs sur leur carrière. Treize professeures ont pris part des entrevues semi‐ structurées axées sur six thèmes clés : les bienfaits retirés des participations à des projets internationaux, les facteurs jouant sur la motivation, les catalyseurs et les obstacles, l’élargissement des visions du monde personnelles et professionnelles et les façons d’acquérir des compétences internationales. Des suggestions sont fournies pour inciter les universitaires de sexe féminin à profiter des débouchés internationaux. Mots clés : promotion de la carrière des femmes, universitaires de sexe féminin, internationalisation